THE BIRTH WEIGHT CHARACTERISTICS IN RURAL AND URBAN AREAS IN THE PROVINCE OF NORTH SUMATERA, INDONESIA - Tri Bayu Purnama; Windi Aulia (Universitas Airlangga, 2023)
The infant mortality rate remains public health problem. Low birth weight prevalence has been estimated around 60%-80% of all neonatal deaths. Birth weight problems can be associated by infant factors, demographic factors, and maternal factors. Likewise, the difference in area of residence that can affect birth weight. This study aims to investigate the differences birth weight both rural and urban areas in North Sumatera. This study used secondary data which is originated from the Indonesia Demographic Health Survey (IDHS) in 2017. The sample of this study was 991 children. The existence of a process of data elimination due to missing data, thus obtaining 499 children who were used as research samples. Data analysis used the Mann Whitney test to see if there was a difference in the average birth weight between variables. Most of the baby's weight was born within normal limits as much as 85.6%. The results of the Mann Whitney test show that there is a relationship between birth weight and area of residence and birth weight in rural areas is higher than in urban areas.